War and body in César Vallejo’s España, aparta de mí este cáliz - Muñoz Carrasco, Olga (Revista Chilena de Literatura, 2022)
The poetry book España, aparta de mí este cáliz by César Vallejo shows his commitment with the Republican side during the Spanish Civil War. War is reflected through the body in different ways: combatants react as if they were only one body, the poet struggles with his writing within his limited flesh, battles take place within the corporal limits of soldiers’ bodies, and the country whose universal destiny is at risk appears as a mother carrying her womb in agony. This paper studies how the constant presence of the body in Vallejo’s works reaches both a metaphorical and a literal plenitude in this book, which enables the defense of the República.